Polymer‐Fullerene Network Formation via Light‐Induced Crosslinking. Issue 17 (23rd June 2016) - Sugawara, Yuuki; Hiltebrandt, Kai; Blasco, Eva; Barner‐Kowollik, Christopher
Abstract : A facile and efficient methodology for the formation of polymer‐fullerene networks via a light‐induced reaction is reported. The photochemical crosslinking is based on a nitrile imine‐mediated tetrazole‐ene cycloaddition reaction, which proceeds catalyst‐free under UV‐light irradiation ( λ max = 320 nm) at ambient temperature. A tetrazole‐functionalized polymer ( M n = 6500 g mol −1, Ð = 1.3) and fullerene C60 are employed for the formation of the hybrid networks. The tetrazole‐functionalized polymer as well as the fullerene‐containing networks are carefully characterized by NMR spectrometry, size exclusion chromatography, infrared spectroscopy, and elemental analysis. Furthermore, thermal analysis of the fullerene networks and their precursors is carried out. The current contribution thus induces an efficient platform technology for fullerene‐based network formation. Abstract : A novel avenue for polymer‐fullerene network formation is demonstrated by employing light‐induced chemistry based on tetrazole cycloaddition. The networks can be readily fabricated by simple UV irradiation of a tetrazole‐functionalized polymer in the presence of fullerenes.